PELATIHAN BAGI SISWA PALANG MERAH REMAJA DALAM MEMBERIKAN PERTOLONGAN PERTAMA PADA LUKA - Eva Susanti; Prahardian Putri (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
The incidence of injuries is increasing every year, both acute and chronic wounds. A recent study in America showed the prevalence of patients with wounds was 3.50 per 1000 population. The majority of wounds in the world's population are wounded due to surgery/trauma (48.00%), foot ulcers (28.00%), pressure sores (21.00%). To be able to understand and provide first aid to wounds so that the Adolescent Red Cross students have good skills in the community. This training was carried out using the demonstration method and simulation of first aid for wounds. Results: Implementation of wound care education and training to provide knowledge, understanding of the need for wound care for Red Cross Teenagers High School Muhammadiyah 2 Palembang. There is an understanding of the Red Cross Teenagers of Muhammadiyah Middle School in Palembang after counseling about injuries. And participants can perform or demonstrate first aid training for wounds carried out according to procedures.